Tango of Slaves
“Tango of Slaves,” named after a popular tune from the Warsaw Ghetto, is the filmmaker’s effort to give his two daughters, their own images of the Holocaust and their family history. The film follows the filmmaker and his father as they return to Warsaw, Poland in a physical journey that becomes a meditative essay about history, memory, and their preservation in imagery. Alternating between telling his father's story, the present futile search for documentary proof of it, and a critical reading of the images that did survive the Ghetto, the film raises an important issue concerning one generation's ability to accurately pass its history on to the next.